Five Essays on Experimental Finance - Gärtner, Florian; Justus Liebig University Giessen (My University, 2023)
The dissertation focuses on two topics: First, it investigates very basic financial decisions. It models these decisions in experiments. The results show that the participants in these experiments fail to identify the optimal decision surprisingly often. These errors have systematic components, but through nudging and boosting interventions, it is possible to reduce them. Second, it investigates whether the specific knowledge about sustainable financial products increases the propensity to invest sustainably. The Dissertation shows that it does, provided a sufficiently favorable preference for sustainability.
Keywords: Experimental Finance; Sustainable Finance; Behavioral Finance; ddc:330